Pleiotropic and epistatic genes in sickle cell anaemia - Nagel, Ronald (Henry Stewart Talks, 2007)
Determination of pleiotropic genes, Search for polymorphic genes among the pleiotropic genes as candidates for epistasis, Known epistatic effects, Kidney pathology in sickle cell disease, Renal disease epidemiology, Panoply of transgenic mice, Involvement of metabolic pathways in constitutive chronic kidney damage in Tx mice, Hypoxia, Mediators of oxidative stress, Up and down regulated genes, HO- 1 histopathology, The effect of sickle red blood cell adhesion on gene expression in PAF pre-treated microcirculatory bed, Von Willebrand factor (vWF) and sickle cell anemia, vWF, shear stress and sickle cell anaemia, Epistatic genes may open new therapeutic strategies for SS disease, PAF induces the up-regulation of a number of genes that have the capacity of protecting the endothelium, stem cells and other hematopoetic precursors
Archived at 2021/02/25